Corporate Law Federalism in Historical Context: Comparing Canada and the United States - Hutchison, Camden (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2018)
Although American and Canadian corporate law share many similarities, they are also marked by important institutional differences. Among the most notable are the differing roles of federal versus state/provincial policymaking in the two countries: while American corporate law has been deeply influenced by jurisdictional competition among the states, Canadian law has instead been shaped by federal legislative activity, as seen today in the standardizing influence of the Canada Business Corporations Act. These different institutional histories have led to distinct evolutionary paths, with important substantive consequences for contemporary corporate law.Despite considerable academic attention to the subject of corporate law federalism, these historical differences between Canada and the United States are not well understood. This article explains why jurisdictional competition arose in the United States but not Canada by examining the “Great Merger Movement” of the late nineteenth and early twentieth centuries. Specifically, this article makes three related arguments: (1) in the United States, the rise of jurisdictional competition was driven not by corporate governance issues, as is often assumed, but rather by the desire to avoid state and federal antitrust restrictions; (2) for a variety of reasons, cartelization and price fixing were more viable in Canada than the United States, delaying the onset of consolidative mergers; and (3) when the Canadian merger movement finally arrived, Canadian federal company law readily facilitated industrial consolidation, reducing the incentives for individual provinces to compete to attract company charters.The different experiences of Canada and the United States reveal an intriguing historical irony—while Canadian corporate law is sometimes criticized as lacking in competitive responsiveness, the roots of this complacency are closely tied to the turn-of-the-century merger movement, in which Canadian law was less restrictive than its traditional American counterpart.